Identification of two novel HIV-1 circulating recombinant forms of CRF111_01C and CRF116_0108 in southwestern Yunnan, China. Issue 1 (31st December 2022) - Ye, Mei; Chen, Xin; Duo, Lin; Ma, Jin; Cao, Le; Zhang, Chiyu; Zheng, Yong-Tang
ABSTRACT: Yunnan, the region hardest hit by HIV/AIDS in China, is also an area with the most abundant HIV-1 genetic diversity. A large number of novel HIV-1 circulating recombinant forms (CRFs) and unique recombinants were identified among injection drug users in Yunnan; however, few were found among sexual contacts. Here, we obtained 15 near full-length genome sequences (NFLGs) from HIV-1 seropositive heterosexual contacts in Yunnan who received antiretroviral therapy during the period from 2014 to 2016. Phylogenetic analysis showed that six NFLGs belonged to CRF01_AE (n = 3) and CRF106_cpx (n = 3), and the other nine sequences were novel inter-subtype recombinants. Of the recombinants, two novel CRFs (CRF111_01 C (n = 4) and CRF116_0108 (n = 4)) and one CRF106_cpx variant (n = 1) were identified. CRF111_01 C had a CRF01_AE backbone with seven subtype C fragments inserted into the gag, pol, vif, env, nef and 3ʹLTR regions. CRF116_0108 had a CRF08_BC backbone with a CRF01_AE fragment inserted into the pol, tat, rev, vif, vpr, vpu and env regions. Phylogeographic analyses estimated that CRF111_01 C and CRF116_0108 originated approximately 1995.7–1998.6 and 1991.7–1993.7, respectively. These identifications of two novel HIV-1 CRFs highlighted the importance of continuous surveillance in heterosexual contacts and other high-risk groups in this region and the surrounding regions.